Edible freshwater snail (Paludomas conica) attenuates STZ‐induced diabetic complications by regulating PFK‐1 and PON‐1 gene expression. (11th December 2022) - Rafi, Md. Khalid Juhani; Rahman, Md. Atiar; Siddique, Tanvir Ahmed; Bithy, Farhana Yesmin; Akter, Sumaiya; Aktar, Rasheda; Nisa, Fatema Yasmin; Khan, Md. Asif Nadim; Hossain, Md. Altaf; Saha, Srabonti; Ahmed, A. M. Abu
Summary: Freshwater invertebrates, especially molluscs, have recently piqued the interest of researchers as a potential new source of food protein hydrolysates. This study prepared bioactive protein hydrolysates (PPh) from the freshwater snail Paludomas conica and investigated their antioxidant and antidiabetic effects by evaluating biochemical and molecular approaches. The DPPH free radical assay, ABTS scavenging assay, FRAP assay and superoxide scavenging assay investigated the antioxidant effects. The antidiabetic potential was measured in α‐amylase and α‐glucosidase inhibition assays followed by in vivo assay in streptozotocin (STZ)‐induced diabetic animal model and gene expression studies. In all antioxidant experiments, the half‐maximal inhibitory concentration (IC50 ) of PPh was less than the cut‐off value, 1000 μg/mL. The inhibitory concentration of PPh was 1.89 mg/mL for α‐amylase and 334.70 μg/mL for α‐glucosidase in vitro assay. Furthermore, in the streptozotocin‐induced Wistar albino rats model of six groups ( n = 5, body weight 180–20 g, age 6–7 weeks), the administration of PPh 250 mg/kg for diabetic rats a 4 weeks intervention attenuated elevated glucose levels and other diabetes‐related biomarkers (alanine aminotransferase, aspartate aminotransferase, lipid profile, total protein, uric acid). Molecular assay by the qPCR analysis showed a significant ( P < 0.05) upregulation of the relative mRNA expression of antioxidant and glucose metabolism‐regulating enzymes‐related genes of superoxide dismutase (SOD‐1), Paraoxonase‐1 (PON1) and Phosphofructokinase‐1 (PFK1). Findings demonstrate that PPh could be used as a potential food source to reduce diabetic complications by regulating gene expression of antioxidant and glycolytic enzymes. Abstract : Paludomas conica in regulating the gene expressions to attenuate diabetic complications.